Regular human insulins versus rapid-acting insulin analogues in children and adolescents with type 1 diabetes: a protocol for a systematic review with meta-analysis and Trial Sequential Analysis - Johanne Juul Petersen; Sophie Juul; Caroline Barkholt Kamp; Pascal Faltermeier; Christina Dam Bjerregaard Sillassen; Tiago Jeronimo Dos Santos; Janus Christian Jakobsen (Systematic Reviews)
Abstract Background Type 1 diabetes is a serious, chronic disorder with an increasing incidence among children and adolescents. Glycemic control in individuals with type 1 diabetes is better managed through a basal-bolus regimen with either regular human or rapid-acting insulin analogues administered as a bolus at mealtimes. Rapid-acting insulin analogues have been hypothesized to cause optimal glycemic control and less risk of hypoglycemic episodes compared to regular human insulins. However, this has never been systematically assessed in children and adolescents with type 1 diabetes. Therefore, this systematic review aims to assess the beneficial and harmful effects of regular human insulins versus rapid-acting insulin analogues in children and adolescents. Methods This is a protocol for a systematic review. A search in major medical databases (e.g., MEDLINE, EMBASE, CENTRAL) and clinical trial registries will be performed by a search specialist. We will include published and unpublished randomized clinical trials comparing regular human insulins versus rapid-acting insulin analogues (lispro, aspart, or glulisine). Two review authors will independently extract data and conduct risk of bias assessments. Primary outcomes will be severe hypoglycemia, ketoacidosis, and serious adverse events. Secondary outcomes will be quality of life, HbA1c, and non-serious adverse events. Data will be analyzed using fixed-effect meta-analyses, random-effects meta-analyses, and Trial Sequential Analysis. Several subgroup analyses are planned. Risk of bias will be assessed with the Cochrane Risk of Bias tool—version 2, an eight-step procedure will be used to assess if the thresholds for clinical significance are crossed, and the certainty of the evidence will be assessed by Grading of Recommendations, Assessment, Development and Evaluations (GRADE). Discussion The beneficial and adverse effects of regular human insulins versus rapid-acting insulin analogues have not been systematically assessed in children and adolescents. There is a need for a comprehensive systematic review of the current evidence. Systematic review registration PROSPERO: CRD42024508625.